Economic perspective of ethanol and biodiesel coproduction from industrial hemp. (25th May 2021) - Viswanathan, Mothi Bharath; Cheng, Ming-Hsun; Clemente, Tom Elmo; Dweikat, Ismail; Singh, Vijay
Abstract: In this study, the economics of producing biofuels from an industrial hemp (Cannabis sativa) genotype – 19m96136 was investigated. A lignocellulosic biofuel plant, hourly consuming 85 metric tons of hemp biomass was modeled in SuperPro Designer®. The integrated bioenergy plant produced hemp biodiesel and bioethanol from lipids and carbohydrates, respectively. The structural composition of the industrial hemp plant was analyzed in a previous study. The data obtained was used to simulate feedstock composition in SuperPro Designer®. The simulation results indicated that Hemp containing 2% lipids can yield up to 3.95 million gallons of biodiesel annually. On improving biomass lipid content to 5 and 10%, biodiesel production increased to 9.88 and 19.91 million gallons, respectively. The breakeven unit production cost of hemp biodiesel with 2, 5, and 10% lipid containing hemp was 18.49, 7.87, and 4.13/gallon, respectively. The biodiesel unit production cost when utilizing 10% lipid-containing hemp was comparable to soybean biodiesel at 4.13/gallon. Furthermore, sensitivity analysis revealed the possibility of a 7.80% reduction in unit production cost upon a 10% reduction in hemp feedstock cost. Furthermore, industrial hemp was capable of producing between 307.80 and 325.82 gallons of total biofuels per hectare of agricultural land than soybean. Highlights: Between 3.95 and 19.91 million gallons/yr of biodiesel can be produced from industrial hemp containing 2–10% lipids. The breakeven unit production cost (UPC) of hemp biodiesel varied between 18.49 and 4.31/gallon biodiesel. At 10% lipid concentration in hemp biomass, the UPC is comparable to soybean biodiesel. A hectare of industrial hemp can produce 51% more biodiesel than soybean.